Investigation of constitutive models and microstructure evolution during hot deformation and solution treatment of Al–Zn–Mg–Cu alloy - Dejin Wei; Luyi Han; Zhengfeng Lv; Guangchun Wang; Guoqun Zhao (Journal of Materials Research and Technology, 2024)
In this paper, isothermal thermal compression tests were carried out on Al–Zn–Mg–Cu alloys at varying deformation temperatures (360°C∼440°C) and strain rates (0.001s−1∼10s−1) using a Gleeble-3500C thermal simulation tester. Based on the true strain stress data obtained from the tests, the flow behavior of Al–Zn–Mg–Cu alloys during thermal deformation was investigated. Through a comprehensive consideration of deformation temperature, strain rate, and strain compensation, a high-precision constitutive model was established. Additionally, the specimens subjected to hot compression were further treated with solution annealing for different durations (0 h–2 h) to investigate the static recrystallization (SRX) behavior and the associated microstructural evolution of the alloy during the solution treatment process. Electron Backscatter Diffraction (EBSD) was employed to characterize the microstructure evolution of Al–Zn–Mg–Cu alloy under various deformation and solution treatment conditions. The EBSD data were further processed and analyzed using the MTEX toolbox. The results revealed that dynamic recovery (DRV) is the predominant softening mechanism during the deformation process, accompanied by a small amount of dynamic recrystallization (DRX). The dynamically recrystallized grains exhibit a random crystallographic orientation. Further investigation showed that low temperature and high strain rate conditions are unfavorable for the occurrence of dynamic recovery and dynamic recrystallization during the thermomechanical processing. However, dislocations accumulated during deformation provided sufficient stored energy for the growth of static recrystallized grains during subsequent solution treatment, with static recrystallized grains predominantly forming at grain boundaries.